2014
DOI: 10.1101/gad.248864.114
|View full text |Cite
|
Sign up to set email alerts
|

Differential spatial and structural organization of the X chromosome underlies dosage compensation in C. elegans

Abstract: The adjustment of X-linked gene expression to the X chromosome copy number (dosage compensation [DC]) has been widely studied as a model of chromosome-wide gene regulation. In Caenorhabditis elegans, DC is achieved by twofold down-regulation of gene expression from both Xs in hermaphrodites. We show that in males, the single X chromosome interacts with nuclear pore proteins, while in hermaphrodites, the DC complex (DCC) impairs this interaction and alters X localization. Our results put forward a structural mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 39 publications
1
53
3
Order By: Relevance
“…This is in contrast to dosage compensation in mammals where in cells carrying two X chromosomes, one of the X chromosomes is inactivated while dosage-sensitive genes in the other are upregulated (Deng et al 2011). A key component of the dosage-compensation machinery in C. elegans is the dosage compensation complex (DCC), which is structurally similar to the condensin complex that can induce structural changes to DNA (Sharma et al 2014;Lau and Csankovszki 2015). Both FISH and Hi-C data suggest that the DCC leads to compaction of chromosome X in XX animals.…”
Section: Features Of C Elegans Chromosome Organizationmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in contrast to dosage compensation in mammals where in cells carrying two X chromosomes, one of the X chromosomes is inactivated while dosage-sensitive genes in the other are upregulated (Deng et al 2011). A key component of the dosage-compensation machinery in C. elegans is the dosage compensation complex (DCC), which is structurally similar to the condensin complex that can induce structural changes to DNA (Sharma et al 2014;Lau and Csankovszki 2015). Both FISH and Hi-C data suggest that the DCC leads to compaction of chromosome X in XX animals.…”
Section: Features Of C Elegans Chromosome Organizationmentioning
confidence: 95%
“…Sharma et al (2014) examined the nuclear localization of several X-chromosome loci by FISH and live imaging and found that in hermaphrodites, where the two X chromosomes are dosage compensated, there is no preferential nuclear localization. In contrast, in males the single X chromosome is preferentially localized at the nuclear periphery in a DCC-dependent manner.…”
Section: Features Of C Elegans Chromosome Organizationmentioning
confidence: 99%
“…downregulation on the hermaphrodite X[ 1 9 6 _ T D $ D I F F ] chromosomes away from the nuclear periphery[62] …”
mentioning
confidence: 99%
“…DamID is particularly well adapted when one wants to describe chromosome or megabase scale interactions (e.g. localization close to the nuclear lamina or nuclear pores, Gonzalez-Aguilera et al, 2014;Guelen et al, 2008;Pickersgill et al, 2006;Sharma et al, 2014;Towbin et al, 2012). However, many profiles were achieved with nuclear proteins which bind smaller regions, such as transcription factors, RNA polymerase, chromatin remodellers or insulators (Filion et al, 2010;Southall et al, 2013).…”
Section: Damid In C Elegans: Theoretical Considerationsmentioning
confidence: 99%